Student reflections on an interdisciplinary pandemics course utilising systems thinking. (26th August 2022) - Shelley, Karen; Osborne, Nicholas J.; Reid, Simon; Willemsen, Angela; Lawler, Sheleigh
Abstract: Issue addressed: The complexity and uncertainty of the COVID‐19 pandemic highlights the need to change training of public health professionals in higher education by shifting from siloed specialisations to interdisciplinary collaboration. At the end of 2020 and 2021, public health professionals collaboratively designed and delivered, a week‐long intensive course—Public Health in Pandemics. The aim of this research study was to understand whether the use of systems thinking in the design and delivery of the course enabled students to grasp the interdisciplinary nature of contemporary health promotion and public health practice. Research methods: Two focus group interviews ( n = 5 and 3/47) and a course opinion survey ( n = 11/47) were utilised to gather information from students regarding experiences and perceptions of course design and delivery, and to determine if students felt better able to understand the complex nature of pandemics and pandemic responses. Major findings: Students provided positive feedback on the course and believed that the course design and delivery assisted in understanding the complex nature of health problems and the ways in which health promotion and public health practitioners need to work across sectors with diverse disciplines for pandemic responses. Conclusions: The use of an integrated interdisciplinary approach to course design and delivery enabled students used systems thinking to understand the complexity in preparing for and responding to a pandemic. This approach may have utility in preparing an agile, iterative and adaptive health promotion and public health workforce more capable of facing the challenges and complexity in public health.